Prevalence of Antimicrobial Resistance in Select Bacteria From Retail Seafood—United States, 2019 - Tate, Heather; Ayers, Sherry; Nyirabahizi, Epiphanie; Li, Cong; Borenstein, Stacey; Young, Shenia; Rice-Trujillo, Crystal; Saint Fleurant, Sanchez; Bodeis-Jones, Sonya; Li, Xunde; Tobin-D’Angelo, Melissa; Volkova, Victoriya; et al. (Frontiers in Microbiology, 2022)
In 2019, the U.S. National Antimicrobial Resistance Monitoring System (NARMS) surveyed raw salmon, shrimp, and tilapia from retail grocery outlets in eight states to assess the prevalence of bacterial contamination and antimicrobial resistance (AMR) in the isolates. Prevalence of the targeted bacterial genera ranged among the commodities: Salmonella (0-0.4%), Aeromonas (19-26%), Vibrio (7-43%), Pseudomonas aeruginosa (0.8-2.3%), Staphylococcus (23-30%), and Enterococcus (39-66%). Shrimp had the highest odds (OR: 2.8, CI: 2.0-3.9) of being contaminated with at least one species of these bacteria, as were seafood sourced from Asia vs. North America (OR: 2.7; CI: 1.8-4.7) and Latin America and the Caribbean vs. North America (OR: 1.6; CI: 1.1-2.3) and seafood sold at the counter vs. sold frozen (OR: 2.1; CI: 1.6-2.9). Isolates exhibited pan-susceptibility (Salmonella and P. aeruginosa) or low prevalence of resistance (<10%) to most antimicrobials tested, with few exceptions. Seafood marketed as farm-raised had lower odds of contamination with antimicrobial resistant bacteria compared to wild-caught seafood (OR: 0.4, CI: 0.2-0.7). Antimicrobial resistance genes (ARGs) were detected for various classes of medically important antimicrobials. Clinically relevant ARGs included carbapenemases (blaIMI-2, blaNDM-1) and extended spectrum β- lactamases (ESBLs) (blaCTX-M-55). This population-scale study of AMR in seafood sold in the U.S. provided the basis for NARMS seafood monitoring, which began in 2020.